(3CKQ GdJbOe aj JcfhdhLjG GdeYdheGJ Ydi GdNUGFU GdfhYjI h GdcejI ddehGQO GdHTQjI (B/s - (3GMeO TcQ, djdi MSGe GdOjfs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 2011)
(3CgejI h JWhQ JcfhdhLjG GdeYdheGJ h CKQ GdJbOe aj gPg GdJcfhdhLjG Ydi GdNUGFU GdfhYjI h GdNUGFU GdcejI ddehGQO GdHTQjI , GdaLhI GdeYQajI aj GdOQGSGJ GdSGHbI h GdHMhK GdeSJbHdjI GdebJQMI(B.s
Keywords: (3GdehGQO GdHTQjIs; (3JcfhdhLjG GdeYdheGJs